Pathology of Perineural Spread - Brown, Ian S. (Journal of Neurological Surgery Part B: Skull Base, 2016)
The perineural space is a compartment located between the nerve axons, supporting cells and tissues, and the epineural fibrous sheath. Tumor cells invade this space in response to a complex interplay of trophic factors in the local microenviroment. This attraction of tumor cells to nerves is referred to as neurotropism. The perineural space provides a conduit for tumor spread beyond the primary site of tumor occurrence. Perineural tumor growth is of two types: perineural invasion, affecting small unnamed nerves; and perineural spread, affecting larger, named nerves and presenting with clinical symptoms related to the involved nerve. Both forms of perineural tumor growth represent an adverse prognostic feature and are an essential element of the histopathologic reporting of malignancies of the head and neck region. Perineural spread is associated with decreased overall survival. Endoneurial invasion frequently accompanies perineural spread. The epineurium is more resistant to invasion and represents an important barrier to tumor spread. Immunohistochemical stains such as broad-spectrum keratin can aid in defining the proximal extent of perineural tumor spread.
Keywords: perineural invasion; perineural spread; endoneurium; epineurium; neurotropism